Northern Bobwhite Home Range Sizes and Movements in South Texas - Katherine S. Miller; Fidel Hernández; Leonard A. Brennan; Randy W. DeYoung; X. Ben Wu (National Quail Symposium Proceedings, 2017)
Northern bobwhites (Colinus virginianus) often have relatively small home ranges (1-km radius); however, occasional long-distance movements also have been recorded, which may help maintain connectivity and genetic diversity within and among populations. We quantified movements of radiocollared northern bobwhites on the King Ranch in South Texas, USA. For each bird we determined core area, home range (fixed kernel), mean movement rate, and maximum distance moved. We compared movements across age, gender, precipitation trends, and plant communities using Mann–Whitney U and Kruskal–Wallis tests. Almost half (44.7%) of the birds moved >400 m (max. distance moved) and 46 (16%) moved >1 km over the course of the study. Males had higher movement rates (juvenile x̄ = 54.9 m, SE = 1.77 m, n = 64; adult x̄ = 56.6 m, SE = 1.95 m, n = 65) than females (juvenile x̄ = 51.26 m, SE = 1.80 m, n = 102; adult x̄ = 48.14 m, SE = 1.49 m, n = 62; χ23,289 = 14.90, P = 0.02). Maximum distance moved was longer in dry years (609.8 ± 136.3 m) compared with normal or moist years (x̄ = 542.8 m, SE = 47.0 m; x̄ = 536.6 m, SE = 28.8 m, respectively, n = 293). Northern bobwhites moved farther in dry years, possibly to find cover and food. A small percentage made relatively long-distance movements (n = 18, 6%, >1.6 km, max. 6.5 km). These rare movements may influence gene flow and genetic structure of northern bobwhite populations in South Texas.
Keywords: colinus virginianus; northern bobwhite; habitat; Palmer Modified Drought Index; South Texas; Texas Ecological Land Classification Project